Analisis Perencanaan Strategi dan Inovasi terhadap Keunggulan Bersaing - Nevi Afriani Afriani; R. Deni Muhammad Danial; Kokom Komariah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The study aims to determine how much influence strategic planning and innovation have on competitive advantage in Sukabumi City Traditional food Smes. Respondents in this study totaled 70 people who were shown to MSME actors in Sukabumi City Traditional Snacks. This research method uses quantitative research methods with an assosiciative descriptive approach and the sample technique used is saturated sample technique. In this study, the normality test, simultaneous statistical test (F test)and partial statistical test (T test) werecarried out. The results of this study indicate that there is a significant influence between strategic planning, innovation and competitive advantege with a result of 38.670>3.134,which means that the calculated F value is greaterthan the F table. In strategic planning (X1) it has a significant effect on competitive advantage (Y), this is evidenced by the value obtained from the result of T count>T table (2.180>1.667). Innovation (X2) has a significant effect on competitive advantage (Y), this is evidenced with a calculated T value that is greater than T table (5.106>1.667).